2014
DOI: 10.1111/ijn.12283
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational intervention on hand hygiene compliance and infection rate in a developing country neonatal intensive care unit

Abstract: Nosocomial infections are a significant problem in neonatal intensive care units (NICUs) and hand hygiene (HH) has been stated as an effective mean to prevent spread of infections. The aim of study was to assess the baseline compliance HH practices and to evaluate the impact of hand washing educational programme on infection rate in a NICU. Continuous surveillance of nosocomial infections was done. A total of 15,797 and 12 ,29 opportunities for HH were observed in pre-intervention and postintervention phases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…In another study, participants in a survey in the Neonatal ICU reported that among the factors that prevent infections the HH using the product in one of them, including to clean material (20) Many times, HH gives the impression of taking long time and becomes the reason for lack and low adherence (13) . However, several studies suggest that alcohol gel dispensers and reminders promote an improvement to HH adherence, resulting in lower rates of nosocomial infections (5,12,21) . In order to improve HH, WHO brings the multimodal strategy guide presenting key components, such as System change -alcoholic solution in service points, availability of water, soap and paper towels; Training/education; Evaluation and feedback; Reminders in the workplace; Institutional safety climate -participatory management (2,21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, participants in a survey in the Neonatal ICU reported that among the factors that prevent infections the HH using the product in one of them, including to clean material (20) Many times, HH gives the impression of taking long time and becomes the reason for lack and low adherence (13) . However, several studies suggest that alcohol gel dispensers and reminders promote an improvement to HH adherence, resulting in lower rates of nosocomial infections (5,12,21) . In order to improve HH, WHO brings the multimodal strategy guide presenting key components, such as System change -alcoholic solution in service points, availability of water, soap and paper towels; Training/education; Evaluation and feedback; Reminders in the workplace; Institutional safety climate -participatory management (2,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in developing countries, such as Brazil, HAIs is an important cause of morbidity and mortality in the Neonatal Intensive Care Units (Neonatal ICU). Firstly, it is because in neonates the risk of infection is higher due to the immaturity of the immune system, invasive procedures for life support, and the use of medications (5) . Children in Pediatric Intensive Care Units (Pediatric ICU) often have factors as crucial conditions for the contamination through infection, such as congenital or acquired immunodeficiencies, immunosuppressant use, and prolonged length of hospital stay with infection rates ranging from 3% to 27% than adult intensive care units (ICU) (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e hand washing does not remove all local bacteria, as the resident fl ora is strongly attached to the skin; nevertheless, the pathogenic bacteria (S. aureus, Gram-negative bacteria, yeasts) that are associated with healthcare-related infections are commonly part of transient fl ora, and more susceptible to hand washing [31]. Th us, this simple gesture can significantly decrease the rate of nosocomial sepsis [32].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of the nursing and midwifery role is indicated in epidemiological enquiry to support service planning, for example, for prevention of preterm birth and post‐disaster care; in health education and promotion such as for breastfeeding, smoking cessation and teen pregnancy; patient and family advocacy for people living with physical and mental disability and frailty; nursing care and interventions, including complementary and alternative health; the significant impact of doing simple things well, for example hand hygiene preventing neonatal sepsis . This issue also reflects wider roles in advancement of policy and science.…”
mentioning
confidence: 99%